Współczesne warunki współdziałania na wsi - Kożuch, Antoni (Co-operation in Rural Areas - Present Conditions, 2005)
The debate over the role of co-operation and collaboration in transition economies has proceeded largely at the level of theory with relatively little empirical work. This papers aims to fill a part of this gap by examining Polish experience. In the paper the attempt is made to show conditions of effective co-operation in agricultural sector and in rural economy. A thesis that co-operation is the main factor of rural development is proved. Increase of competitiveness presently depends not only on quality of farm produce, on productivity of agricultural and rural economic units, but mainly on co-operation between these units. Present internal and external conditions are described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 496-500